Special Topic Forum On Innovation In Business Networks From A Supply Chain Perspective: Current Status and Opportunities for Future Research. Issue 4 (21st October 2013) - Arlbjørn, Jan Stentoft; Paulraj, Antony
Abstract : This editorial introduces the special topic forum on "innovations in business networks from a supply chain perspective." Additionally, it highlights the gap between the importance attributed by practice and the current state of academic research focusing on the confluence of innovation and supply chain perspectives. By specifically assessing the current status of research as well as practice, this paper not only identifies the key issues in current research and proposes an agenda for future research, but also points out the challenges that scholars will encounter in pursuing the proposed research agenda.